Fixed Point Theorems for Monotone Caristi Inward Mappings - Jorquera-Alvarez, E (Taylor and Francis Inc., 2018)
In this paper, we introduce the monotone Caristi inward mappings. As an example, we show that monotone inward contraction mappings are monotone Caristi inward mappings. A general fixed point theorem for such mappings is given. A mutlivalued version of these results is also introduced. © 2018, © 2018 Taylor & Francis.